Study of shoot tip necrosis problems of Fegra fig (Ficus palmata Forssk.) in vitro in Saudi Arabia - Al-Aizari, Ahmed Ali; Dewir, Yaser Hassan; Al-Obeed, Rashid Sultan; Al-Saif, Adel M.; Almutairi, Khalid F.; Murthy, Hosakatte Niranjana; Mansor, Hakiman (American Society for Horticultural Science, 2024)
This work studied the micropropagation of fegra fig (F. palmata Forssk.) during which we experienced the incidence of shoot-tip necrosis (STN). STN was evident during the shoot elongation stage, which was regenerated on Murashige and Skoog (MS) medium supplemented with 2 mg/L 6-benzylaminopurine. To alleviate SNT, we conducted a series of experiments and supplemented the medium with calcium chloride (40, 80, and 120 mg/L), ascorbic acid (50, 100, and 150 mg/L), silver nitrate (1, 2, and 3 mg/L), and boric acid (9.3, 12.4, and 15.5 mg/L). Results showed that all the treatments controlled STN at varying levels, and supplementation of medium with 3 mg/L silver nitrate reduced the incidence of STN from 80% to 24%. The regenerated shoots were rooted on the same medium with incubation of cultures in the dark for 3 weeks and subsequent 4 weeks of incubation under 16/8-hour light/dark photoperiod. The growth parameters (number of shoots and roots, length of the main shoot and root, fresh and dry weights), photosynthetic pigments (chlorophylls and carotenoids), and relative water content of plantlets were restored with the application of 3 mg/L silver nitrate to the medium. Incubation of cultures initially in the dark followed by 16/8-hour light incubation facilitated axillary shoot elongation. On the basis of our findings, it is recommended to culture the regenerated axillary shoots of fegra fig onto MS medium containing 3% sucrose, 1.5 mg/L activated charcoal, and 3 mg/L silver nitrate to manage STN effectively.